2010
DOI: 10.1007/dcr.0b013e3181ceeb22
|View full text |Cite
|
Sign up to set email alerts
|

Sacral Nerve Neuromodulation Is Effective Treatment for Fecal Incontinence in the Presence of a Sphincter Defect, Pudendal Neuropathy, or Previous Sphincter Repair

Abstract: Sacral nerve neuromodulation results in a significant improvement in fecal incontinence and Fecal Incontinence Quality of Life scores after medium-term follow-up, even when there is a sphincter defect or pudendal neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(74 citation statements)
references
References 14 publications
3
68
1
2
Order By: Relevance
“…In our long-term outcomes series, one patient who recently benefited from a sacral nerve stimulation device implantation was operated on by our pediatric surgical team together with an adult team before he was entrusted to the adult team. 38,39 We believe this is an important transition for all cases now.…”
Section: Dyssynergic Defecationmentioning
confidence: 83%
“…In our long-term outcomes series, one patient who recently benefited from a sacral nerve stimulation device implantation was operated on by our pediatric surgical team together with an adult team before he was entrusted to the adult team. 38,39 We believe this is an important transition for all cases now.…”
Section: Dyssynergic Defecationmentioning
confidence: 83%
“…This nerve is most commonly damaged in obstetric trauma and is affected by general neuropathy that may be seen in diabetes or multiple sclerosis. 7 This tool measures the time it takes for stimulation of the pudendal nerve, from the ischial tuberosity to the anal canal, to elicit contraction of the pelvic floor muscles. Delayed response is associated with pudendal neuropathy, which can contribute to FI.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study by Brouwer et al showed no correlation between pudendal nerve latency testing with success after sacral nerve stimulation for FI treatment. 7 Other anal physiologic testing includes sensation testing, magnetic resonance imaging (MRI), and endoscopy. Anorectal sensation testing refers to electrical stimulation of the distal anus as well as urge sensitivity of the rectum with balloon inflation.…”
Section: Discussionmentioning
confidence: 99%
“…However, predictive factors that are necessary to reveal the efficacy of sacral neuromodulation prior to performing it remain to be unclear (33,34). The efficacy of sacral neuromodulation in partial sphincter injury has also been demonstrated (35)(36)(37). In patients with scleroderma having proctitis caused by radiation and reduced rectal compliance owing to inflammatory bowel syndrome and in patients with anterior resection or previous rectal prolapse colectomy, the efficacy of sacral neuromodulation is demonstrated only in few studies (38)(39)(40)(41)(42)(43).…”
Section: Gastrointestinal Disordersmentioning
confidence: 99%